Perbedaan Gaya Kepemimpinan di Sekolah yang Bagus dan Kurang Bagus - Anwar, Anwar; Sihombing, Evi; Khairani, Siti; Winara, Winara; Lubis, Wildansyah (Cybernetics: Journal Educational Research and Social Studies, 2024)
This article discusses a comparison of leadership in the context of good and less good schools. Leadership in educational institutions is very important for achieving academic goals and developing student character. However, leadership in good schools, elementary school A and less good elementary school B, has differences in leadership style. This study uses a qualitative approach with data collection techniques through in-depth interviews with school leaders at good schools at elementary school A and less good schools at elementary school B. Data analysis was carried out using the thematic analysis method. The results of the research show that leadership in good schools, Sdn A, is more focused on achieving academic targets, while leadership in less good schools, Sdn B, on the other hand, is not focused on achieving academic targets or anything else. In the context of educational development in Indonesia, this research can provide insight and understanding of the differences in leadership in two different types of educational institutions. It is hoped that the results of this research can provide guidance for leaders of educational institutions in improving the quality of leadership and educational development in Indonesia.